(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
Koçi Bey’s Treatise, one of the fundamental texts reflecting the perception of crisis in 17th-century Ottoman political thought, constructs institutional dissolution through a normative discourse rather than an objective report. Utilizing Cognitive Metaphor Theory (CMT), this study examines how the abstract perception of crisis was built within the political language of the treatise. Through qualitative content analysis, organic and cosmic metaphors such as the “body” (beden), “rose garden” (gülşen), “cover” (libâs), “corpse” (lâşe), and “mirror” (ayna) were categorized into four thematic clusters: state structure, legal status, bureaucratic dissolution, and the restoration of authority (ihya). The findings indicate that these metaphors function not merely as aesthetic rhetorical devices, but as strategic tools that objectify the deterioration of meritocracy as an ontological corruption (fesâd). Consequently, they legitimize the refortification of central authority on Sharia-customary (şer’î-örfî) grounds. The treatise encodes socio-economic upheavals not as an empirical collapse, but as a moral illness requiring healing around the ideal of the classical order (nizâm-ı kadîm). Ultimately, this study aims to provide an interdisciplinary contribution by revealing how historical reality was structured through literary discourse within the Ottoman crisis literature (decline topos).